Exact solutions of (2 - Durur, Hulya; Yokus, Asif (Walter de Gruyter Gmbh, 2021)
The aim of the present study is to obtain different types of hyperbolic type solutions of the (2+1)-Ablowitz-Kaup-Newell-Segur (AKNS) equation. In order to construction exact solutions of AKNS equation, (1/G') expansion method is successfully applied. At the end of this application, singular soliton wave with considerable importance for the shock wave structure and asymptotic behavior employees have emerged. By giving arbitrary values to the constants in the solutions obtained, 3D, 2D and contour graphics are presented. The method used in this article can be used in other nonlinear differential equations (NPDEs) as it is reliable, easy and effective. Ready package programs are used to solve complex and difficult processes in this study.
Keywords: (1/G ')-expansion method; hyperbolic traveling wave solution; singular soliton wave; analytical solution